Guide to confident living - "Peale, Norman Vincent" (London, 2010)
This amazing book will show you the secrets of how to free your inner powers, how to " talk out" your troubles, how to achieve freedom from fear, how to attain married happiness, and how to meet sorrow. Another triumphant breakthrough by the author of " The Power of Positive Thinking."
Keywords: Personal development